Cytotoxic, anti-inflammatory and adipogenic effects of inophyllum D, calanone,isocordato-oblongic acid, and morelloflavone on cell lines - Bakhtiar, M. Taher; Aminuddin, Amnani; Darnis, Deny Susanti; Aminudin, Nurul Iman; On, Shamsul; Ahmad, Farediah; Hamidon, Hanisuhana (The Korean Society of Pharmacognosy, 2016)
This paper reports in vitro cytotoxic, anti-inflammatory and adipocyte diffentiation with adipogenic effects of coumarins inophyllum D (1) and calanone (2), and a chromanone carboxylic acid namely isocordatooblongic acid (3) isolated from Calophyllum symingtonianum as well as a biflavonoid morelloflavone (4) isolated from Garcinia prainiana on MCF-7 breast adenocarcinoma RAW 264.7 macrophages and 3T3-L1 preadipocytes cells, respectively. The cytotoxicity study on MCF-7 cell was conducted by 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) assay. Meanwhile, the study of anti-inflammatory effects in RAW 264.7 macrophages and adipogenic effects on 3T3-L1 pre-adipocytes were conducted through nitrite determination assay and induction of adipocyte differentiation, respectively. In the cytotoxicity study, inophyllum D (1) was the only compounds that exhibited significant cytotoxic effect against MCF-7 cell with IC50 of 84 μg/mL. Further, all by inhibiting the compounds have shown anti-inflammatory effects in lipopolysaccharide (LPS)-induced RAW 264.7 macrophages of nitrite concentration with production. In addition, the compounds also exhibited adipogenic effects on 3T3-L1 pre-adipocytes by stimulating lipid formation. Thus, this study may provide significant input in discovery of the potential effects cytotoxic, anti-inflammatory and adipogenic agents.